2005
DOI: 10.1021/np050291v
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glutamate and Dopamine Receptors in the Psychopharmacological Profile of the Indole Alkaloid Psychollatine

Abstract: Psychollatine (1), a new glycoside indole monoterpene alkaloid isolated from Psychotria umbellata, has shown an interesting psychopharmacological profile. This study aimed to investigate the role of NMDA glutamate and dopamine receptors in mediating the properties of 1. Psychollatine (1) was assessed for NMDA-induced seizures, MK-801-induced hyperlocomotion, amphetamine-induced lethality, and apomorphine-induced climbing behavior in mice. Psychollatine (1) (100 mg/kg) and MK-801 (0.3 mg/kg) prevented NMDA-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…(Rubiaceae) is structurally related to serotonin (Both et al, 2005). Pharmacological studies with psychollatine have shown anxiolytic, antidepressive (Both et al, 2005), and antiseizure activities (Both et al, 2006). Since the detailed phytochemistry of the Rubiaceae species tested in this study is largely unknown, it would be worthwhile to pursue this plant family further.…”
Section: Discussionmentioning
confidence: 99%
“…(Rubiaceae) is structurally related to serotonin (Both et al, 2005). Pharmacological studies with psychollatine have shown anxiolytic, antidepressive (Both et al, 2005), and antiseizure activities (Both et al, 2006). Since the detailed phytochemistry of the Rubiaceae species tested in this study is largely unknown, it would be worthwhile to pursue this plant family further.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in forced swimming test for antidepressant effect, psychollatine (3 and 7.5 mg/kg), was comparable to imipramine (15 mg/kg) and fluoxetine (20 mg/kg) (Both et al 2005). Also, it was suggested that N-methyl-D-aspartate (NMDA) glutamate receptors partially explain psychollatine mechanism of action (Both et al 2006).…”
Section: Psychollatinementioning
confidence: 99%
“…287 The resulting increase in cAMP stimulates the enzymatic activity of PKA, which commands the activation of CREB and therefore the synthesis of anti-apoptotic proteins as well as neuritogenesis. 294 The loss of motor neurons in ALS results from intense glutamate activation of NMDA, followed by massive influx of Ca 2+ , resulting in the activation of calpain, mitogen-activated protein kinase (MAPK) p38, and JNK; NO generation; mitochondrial insults; caspase 3 activation; endoplasmic reticulum (ER) stress; burst in ROS; and ultimately apoptosis, as the antioxidant capacities of SOD are weakened. 288 Furthermore, vinpocetine blocked voltage-gated Na + channels with an IC 50 value equal to 0.3 μM 289 and inhibited the increase of free cytoplasmic Ca 2+ concentration of neurons exposed to veratridine.…”
Section: Indole Alkaloidsmentioning
confidence: 99%